Adoption of the DeLone and Mclean Model to Analyze the Success of Edmodo E-Learning as an Online Learning System During the Covid 19 Pandemic at Dinamika Bangsa University Jambi - Ibnu Sani Wijaya (Lembaga Penelitian dan Pengabdian pada Masyarakat (LPPM) STMIK Global Informatika MDP, 2022)
Edmodo is an online learning platform that is currently widely used in universities in Indonesia during the Covid19 pandemic one of them is at the National Dynamics University (UNAMA) Jambi. In this study, an evaluation of the quality of the Edmodo LMS success was carried out on the Edmodo platforms by adopting themodel Delone And Mclean with 6 variables, namely Information Quality, System Quality, Service Quality, Use, User Statisfaction and Net Benefit. For data analysis using Structural Equation Mode (SEM). Respondents in this study were lecturers and students at UNAMA Jambi who were users of Edmodo. The purpose of this study is to prove the extent of the success of the implementation of Edmodo at the dynamics university of the Jambi nation. Respondents in this study were 166 respondents. Data was collected by means of a survey method. The results of this study indicate the value of R2 with the variables of information quality and system quality has a value of 0.339 categorized as moderate/moderate level. This means that the two dependent variables have a moderate/moderate effect on the dependent variable. For R2, the independent variables use and user satisfaction have substantial/strong values ​​with a value of 0.707, meaning that the two independent variables have an influence and substantial/strong level on the dependent variable